Thoracic Applications of Dual Energy - Remy-Jardin, Martine; Faivre, Jean-Baptiste; Pontana, Francois; Molinari, Francesco; Tacelli, Nunzia; Remy, Jacques (Seminars in Respiratory and Critical Care Medicine, 2014)
Computed tomography (CT) is the core imaging modality for the evaluation of thoracic disorders. With the recently developed dual-energy CT (DECT) technique, the clinical utility of CT in the management of pulmonary diseases can be expanded. The most actively investigated principle of dual energy is material decomposition based on attenuation differences at different energy levels. This technique provides two key insights into lung physiology, that is, regional perfusion and ventilation. This functional information is obtained in addition to morphologic information because high-resolution thoracic anatomy is entirely preserved on dual-energy thoracic CT. The second major possibility offered by DECT is virtual monochromatic imaging that represents a new option for standard chest CT in daily routine. In this review, imaging principles and clinical applications of dual-energy thoracic CT are described. Knowledge of the applications of DECT may lead to wider use of this technique in the field of respiratory disorders.
Keywords: dual-energy computed tomography; chest; perfusion; ventilation